Construction of Epistemology on the Integration of Knowledge from the Perspective of the Quran - Fajri, Muhamad (Universitas Nurul Jadid, 2023)
The Quran is a divine book that encompasses scientific knowledge and has contributed to the development of various branches of knowledge in deferent aspect of life. Therefore, this research aims to discover and analyze Quranic verses related to epistemology and the concept of integrating knowledge from the Quranic perspective. This study is literature review using a philosophical approach and content analysis of three tafsir books, namely Tafsir Ibnu Katsir, Tafsir Jalalyn, and Tafsir Al-Misbah. The Result of the research indicate the existence of verses that synonymous with epistemological activities, such as reading, thinking, observing, reflecting, contemplating, investigating, and so on. Furthermore, it was found that there are two fundamental concept in integrating knowledge from the Quranic perspective. First, it is based on human needs as mentioned in the Quran (An-Nas, Al-Insan, Albashr, and Bani Adam). Second, it is based on the epistemological model of Islamic knowledge (Bayani, Tajrbi, Burhani, and Irfani).